2022
DOI: 10.1016/j.celrep.2021.110279
|View full text |Cite
|
Sign up to set email alerts
|

LFA1 and ICAM1 are critical for fusion and spread of murine leukemia virus in vivo

Abstract: Highlights d LFA1 and ICAM1 are important for cell-contact-dependent spread of MLV in vivo d LFA1 on target cells is critical for MLV cisand trans-infection d ICAM1 on donor cells is critical for MLV cis-infection d MLV fusion is not a limiting step to establish infection in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…In the same study, the authors also showed that M5 protein blocked the parasite translocation of red blood cells by Plasmodium falciparum, irrespective of whether the strain is drug-susceptible or resistant (Bhalla et al 2015 ). Quite recently, ICAM-1/LFA-1 complex has been shown to play an important role in transmission of Murine Leukemia virus between leucocytes, thus, exploiting the host proteins involved in intercellular interactions and barrier function (Engels et al 2022 ). Collectively, it is evident that various microbes exploit host ICAM-1/LFA-1 in cell-to-cell transmission and infection, thus, providing a robust pathway to mitigate microbial infection and persistence.…”
Section: The Role Of Icam-1 In Other Diseasesmentioning
confidence: 99%
“…In the same study, the authors also showed that M5 protein blocked the parasite translocation of red blood cells by Plasmodium falciparum, irrespective of whether the strain is drug-susceptible or resistant (Bhalla et al 2015 ). Quite recently, ICAM-1/LFA-1 complex has been shown to play an important role in transmission of Murine Leukemia virus between leucocytes, thus, exploiting the host proteins involved in intercellular interactions and barrier function (Engels et al 2022 ). Collectively, it is evident that various microbes exploit host ICAM-1/LFA-1 in cell-to-cell transmission and infection, thus, providing a robust pathway to mitigate microbial infection and persistence.…”
Section: The Role Of Icam-1 In Other Diseasesmentioning
confidence: 99%